Atypical hemolytic uremic syndrome due to factor H autoantibody - Uslu-Gökceoğlu, Arife; Doğan, Cagla Serpil; Comak, Elif; Koyun, Mustafa; Akman, Sema (The Turkish Journal of Pediatrics, 2013)
Atypical hemolytic uremic syndrome (aHUS) is a disease caused by pathologies in the alternative complement system. The prevalence of aHUS is 10% of all aHUS cases. The subgroup of aHUS designated as DEAP (DEficiency of CFHR Proteins and CFH Autoantibody Positive)-HUS because of autoantibody to complement factor H (CFH) and CFH-related protein deficiency is seen very rarely, and the prevalence is 6% of all aHUS cases in the literature. We present here a female patient with DEAP-HUS. A 7.5-year-old girl with recurrent attacks of HUS had low C3 level. We initiated plasmapheresis treatment. After further analysis of the complement system, the result was compatible with DEAP-HUS, so we initiated immunosuppressive treatment. There were also family members with deficiency of CFHR-1 and CFHR-3, but they had no CFH autoantibody and no symptoms of HUS. In atypical cases of HUS, we should investigate complement status, especially for factor H autoantibody, for which treatment options differ from those of the other types of aHUS.